Literature Review in Business and Management Sciences: A Suggested Guide for New Researchers - سالم الحصادي سامي; عوض زاقوب علي (Dirasat in Economics and Business, 2026)
The ability to write an effective literature review is a crucial skill for success in academic life, and potentially in professional life as well. This skill requires a combination of integrated abilities that go beyond merely gathering information. A researcher needs to be capable of identifying the research topic, searching for appropriate sources, critically analyzing data, and presenting the findings clearly and logically, often within a limited timeframe. In this context, many researchers, especially newcomers, face significant challenges in mastering this skill, often due to a lack of adequate training. This deficiency makes the task even more difficult. Therefore, this study aims to bridge the knowledge gap for new researchers in the fields of business and management, and social sciences in general, by providing a comprehensive guide to the fundamental steps and principles that should be considered when developing an integrated literature review. This guide covers the essential steps for planning, conducting, and writing a literature review, while also highlighting common mistakes to avoid and the ethical standards that must be observed.